IDENTIFICATION OF UNDERGROUND STRUCTURE OF OPAK FAULT LINE IN PATEN SUBVILLAGE WITH GEOELECTRIC METHOD USING DIPOLE-DIPOLE CONFIGURATION - nabiada maria widyati lisia rini; wibowo Nugroho Budi; Sumardi Yosaphat (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
This research was aimed to determine the distribution of resistivity value and to identifyunderground structure of Opak fault line in Paten subvillage using geoelectric data. Research locationwas located in Paten subvillage, Srihardono village, Pundong subdistrict, Yogyakarta. It hasgeographical coordinates of 7o 56’34,2’’S to 7o56’54.94’’S and 110o21’38.44’’E to 110o21’58.22’’E. Themethod used was geoelectric method with dipole-dipole configuration based on resistivity value of rocks.Data acquisition used Naniura NRD 22 S resistivitymeter. The measurements were conducted for 3 lines.The results showed that the value of resistivity for first line is between 0,056 to 2000 Ωm, second linewas about 0,705 to 2700 Ωm, and for third line was about 2,16-1300 Ωm. Subsurface structure in Opakfault line in Paten is dominated by clay with resistivity value of 1-100 Ωm, limestone with resistivity valueof 500-10000 Ωm and alluvium with resistivity value of 1-20 Ωm .Keywords: geoelectric method, dipole-dipole configuration, Opak fault, Paten subvillage